2021
DOI: 10.2147/rmhp.s303835
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and Adaptation of Behavior in Pregnant Zhuang Women During the COVID-19 Pandemic: A Mixed-Mode Survey

Abstract: Purpose This study explored the impact of COVID-19 on the mental health and adaptation of behavior of Zhuang women in China to provide more specific guidance for the social and medical practice of pregnant women during public health emergencies. Participants and Methods This cross-sectional study recruited 446 pregnant Zhuang women from obstetric outpatient clinics in four tertiary hospitals and online maternity schools in Nanning, Guangxi, between February 24 and March… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 36 publications
1
24
1
Order By: Relevance
“…The finding of the current study was relatively higher than previous studies conducted in Ethiopia during the COVID-19 pandemic (32.2%) ( 9 ), Nigeria (37.5%) ( 28 ), and China (36.77%) ( 29 ). The finding is significantly higher than studies from the Southern Ethiopia (10.04%) ( 26 ), South Africa (23%) ( 18 ), Tanzanian (25%) ( 30 ), China (6.8%) ( 31 ), and (11.18%) ( 27 ), Pakistan (20.4%) ( 32 ), Iran (21%) ( 15 ), Brazil (26.8%) ( 19 ), and Indonesia (29%) ( 33 ).…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…The finding of the current study was relatively higher than previous studies conducted in Ethiopia during the COVID-19 pandemic (32.2%) ( 9 ), Nigeria (37.5%) ( 28 ), and China (36.77%) ( 29 ). The finding is significantly higher than studies from the Southern Ethiopia (10.04%) ( 26 ), South Africa (23%) ( 18 ), Tanzanian (25%) ( 30 ), China (6.8%) ( 31 ), and (11.18%) ( 27 ), Pakistan (20.4%) ( 32 ), Iran (21%) ( 15 ), Brazil (26.8%) ( 19 ), and Indonesia (29%) ( 33 ).…”
Section: Discussioncontrasting
confidence: 84%
“…The odds of experiencing GAD among pregnant women with less than three children were 1.53 times that of pregnant women with greater than three children. Studies in Turkey (37), China (29,38), and Canada (8) support this evidence, in which pregnant women with a lower level of parity had a higher prevalence of anxiety. A higher occurrence of GAD in this study was attributed to major study participants of primigravida (330) 40.9%; this group was more sensitive and could easily magnify pregnancy symptoms such as nausea and vomiting into a more severe illness, which increased the prevalence of anxiety.…”
Section: Discussionmentioning
confidence: 92%
“… 19 In line with this, lockdown and quarantine policies such as social isolation have driven the disturbances of mental wellbeing. 20 …”
Section: Introductionmentioning
confidence: 99%
“…10 Different studies conducted in various parts of the world have reported a wide variety of prevalence of anxiety among pregnant women. Some of the reported prevalence of anxiety are as follows: 39.1% in Nepal, 11 11.1% in India, 12 36.77% in China, 13 37.5% in Nigeria, 14 29.7% in Oman, 15 29.2% in Turkey, 16 and 52% in Netherlands. 17 The prevalence of anxiety reported in this study is lower than most of the other studies conducted in Nepal and other parts of the world.…”
Section: Discussionmentioning
confidence: 99%